PENGELOLAAN BUDIDAYA NILAM (POGESTEMON CABLIN BENTH) DAN PENYULINGAN ATSIRI PADA KELOMPOK TANI DESA BANJARAN DI HUTAN LINDUNG REGISTER 20 PESAWARAN LAMPUNG - M Tahir; Suprapto Suprapto; Dewi Riniarti; Ersan Ersan (DHARMA RAFLESIA, 2018)
Community service program (PPDM) was carried out on Tunas Muda farmer groups, Rente Rejo 1 and Rente Rejo 2. The general purpose of this activity was to provide an added value to the community of protected forest areas by utilizing patchouli from mutation breeding. To preserve the forest, efforts should be made to utilize forest land under tree stands with shade-tolerant plants. The implementation of patchouli cultivation was carried out phasing activities, namely tillage, construction of nursery buildings, procurement of cuttings, nursery maintenance, making planting beds in the field, maintenance with fertilization, weed control, pest control, and harvesting and harvest time . For training activities, implementation has been carried out in the form of direct practice in the field based on cultivation activities. The yield of essential oils obtained by yield between 2.14 - 3.10 percent. Furthermore, the evaluation results show that the average farmer understanding of cultivation activities at the beginning of the new activity reaches 34.21% and the end of the activity has reached 100%. This is supported by chi squared analysis with a value of 5.36 and t table 3.48 of the test level of 5%. The level of income of farmers obtained for one hectare is Rp. 58,750,000.00 for six months or Rp. 9,791,000 / month / ha. This service program (PPDM) illustrates that intensive and measurable mentoring can improve farmers' knowledge in practicing patchouli cultivation with maximum sustainability. Keywords: Patchouli plants, conservation area, good agricultural practises, essential oil.